Determining Impact of Actors and Factors of Supply Chain on the Consumer’s Price of Vegetables in Dhaka City - Hasan Maksud Chowdhury (International Journal of Supply Chain Management, 2017)
This research was aimed to find the impact of actors, seasons and use of e-technology of the supply chain on the consumers price of vegetable in Dhaka city. Most importantly the objective of the research was to determine a consumers price model of the vegetable considering actors and factors as independent variable and price as dependent variable. The researchwas also incorporated new business opportunity of vegetables and an effective supply chain of the vegetable business that would reduce consumers price and spoilage of vegetable. The research was conducted based on primary data collected from farmer, rural retailer, whole-seller, transporter, aratdar, urban whole-seller and retailer and consumer; and on the secondary data, i.e. analysis of the literature, journals, books and different publications. Multiple regression, simulation and percentile techniques were used to analyse data. It was found that intermediate actors like rural and urban whole-seller, retailer, transporter, aratdar; seasons and use of mobile phone greatly affect the consumers price of vegetable in Dhaka city. There are three seasons, up to six intermediate actors and two state of use of e-technology in the supply chain of vegetables. By testing and simulating some initial data the consumers price model of vegetable was proposed Coefficients and constant cost were determined by analysing 349 data and individual impact of e-technology, middle-actors and seasons on consumers price of vegetables were found. KeywordsVegetable supply chain, e-technology, middle-actor, season, aratdar, consumers price and simulation